Platelet-rich Plasma for Androgenetic Alopecia Treatment: A Randomized Placebo-controlled Pilot Study - Paul Gressenberger; Gudrun Pregartner; Thomas Gary; Peter Wolf; Daisy Kopera (Medical Journals Sweden, 2020)
Platelet-rich plasma injections have been presented as an effective treatment for androgenetic alopecia; however, reliable study data concerning this therapy are lacking. The current randomized, placebo-controlled pilot study explored this novel therapy in 30 healthy male subjects with androgenetic alopecia. Five platelet-rich plasma treatments, at intervals of 4-6 weeks, and 2 follow-up examinations were performed. Twenty subjects were injected intracutaneously with platelet-rich plasma and 10 with physiological saline. Treatment efficacy was assessed by changes in hair number and diameter, measured with the TrichoScan system. A secondary objective was to assess clinical improvement, which was evaluated by an independent reviewer using patient photographs and a 5-point Likert scale. In addition, subject satisfaction was assessed by survey. No improvements were seen over the course of the trial, using TrichoScan measurements or visual assessment. In conclusion, these results suggest that treatment with platelet-rich plasma as a monotherapy does not improve hair growth in men with androgenetic alopecia.